Center-Pivot-Irrigated Grain Sorghum Cost-Return Budget in Western Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Haag, Lucas; Holman, John (My University, 2015)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated grain sorghum production in western Kansas.
MF582_2015_04
Keywords: MF582; Economics; Crops; MF